Research on Low Noise Method of Passenger Car Gearbox - Lihong Jin; Hongquan Dong; Fusheng Zhang (Jixie chuandong)
In order to improve the vibration and noise of automobile gearbox， by using the Romax， a dynamics model of the transmission drive system is established， and the dynamic bearing force during the operation of the gearbox is obtained by simulation. The modal analysis is performed on the built finite element box model to learn the box relatively weak areas. The dynamic force of the bearing simulation is used as the excitation of the shell vibration response analysis to analyze the shell vibration characteristics， the shell vibration acceleration is used as the boundary condition， and based on the shell acoustic boundary element model， the modal acoustics transfer method is used to calculate the radiated noise from the sound field outside the casing. By analyzing the modal participation factor and the modal acoustic contribution， the modals which contribute more to vibration noise are determined， and optimization is performed in the corresponding modal vibration sensitive place. The results show that the vibration noise of the optimized gearbox decreases and the radiated noise decreases by 1.4 dB.